Combination effects of azole fungicides in male rats in a broad dose range. (29th April 2016) - Schmidt, F.; Marx-Stoelting, P.; Haider, W.; Heise, T.; Kneuer, C.; Ladwig, M.; Banneke, S.; Rieke, S.; Niemann, L.
Abstract: Two 28-day feeding studies were performed in male rats to investigate combination effects of azole fungicides in a broad dose range. Following separate administration of cyproconazole, epoxiconazole, prochloraz, propiconazole, and tebuconazole at five dose levels, the first three compounds were selected to be administered in two different mixtures at three dose levels including very low doses. Here we present the data obtained by clinical observations, pathology, histopathology, clinical chemistry and haematology. The liver was the common main target organ of all compounds and their mixtures. In addition, epoxiconazole exhibited an effect on the adrenals. Furthermore, food consumption and efficiency and body weight (gain) were affected. Adverse effects of the combinations were observed at dose levels at which the individual substances caused similar effects. No evidence of adverse effects was found at dose levels below the previously established NOAELs. Our findings indicate that the concept of dose additivity appears sufficiently protective for risk assessment of the fungicides examined. Besides toxicological testing, tissue residues of the azole compounds in liver, testis and kidney were determined revealing remarkable differences following administration of the single substances and of the mixtures.